2019
DOI: 10.1002/adma.201901300
|View full text |Cite
|
Sign up to set email alerts
|

Gate‐Tunable and Multidirection‐Switchable Memristive Phenomena in a Van Der Waals Ferroelectric

Abstract: Memristive devices have been extensively demonstrated for applications in nonvolatile memory, computer logic, and biological synapses. Precise control of the conducting paths associated with the resistance switching in memristive devices is critical for optimizing their performances including ON/OFF ratios. Here, gate tunability and multidirectional switching can be implemented in memristors for modulating the conducting paths using hexagonal α‐In2Se3, a semiconducting van der Waals ferroelectric material. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
132
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(144 citation statements)
references
References 40 publications
12
132
0
Order By: Relevance
“…The cross-sectional image and corresponding energy dispersive X-ray spectroscopy (EDS) element mapping at the interface between the multilayer h-BN and α-In2Se3 are shown in Figure 1c, which implies a clean van der Waals heterojunction with negligible interface state trapping effect. Figure 1d shows the Raman spectrum of the channel α-In2Se3 to characterize the material properties, which is consistent with previous reports, 14,18,30 and the peak at 89cm -1 suggests a hexagonal (2H) structure. 18 And the Figure S2b in Supporting Information.…”
Section: Figure 1asupporting
confidence: 89%
See 3 more Smart Citations
“…The cross-sectional image and corresponding energy dispersive X-ray spectroscopy (EDS) element mapping at the interface between the multilayer h-BN and α-In2Se3 are shown in Figure 1c, which implies a clean van der Waals heterojunction with negligible interface state trapping effect. Figure 1d shows the Raman spectrum of the channel α-In2Se3 to characterize the material properties, which is consistent with previous reports, 14,18,30 and the peak at 89cm -1 suggests a hexagonal (2H) structure. 18 And the Figure S2b in Supporting Information.…”
Section: Figure 1asupporting
confidence: 89%
“…Figure 1d shows the Raman spectrum of the channel α-In2Se3 to characterize the material properties, which is consistent with previous reports, 14,18,30 and the peak at 89cm -1 suggests a hexagonal (2H) structure. 18 And the Figure S2b in Supporting Information. Crucially, we transferred the channel α-In2Se3 ferroelectrics onto a conductive Au/Al2O3 substrate and determined its ferroelectric polarization by piezoelectric microscopy (PFM).…”
Section: Figure 1asupporting
confidence: 89%
See 2 more Smart Citations
“…Especially for In 2 Se 3 , it is reported that it still maintains its ferroelectricity and piezoelectricity even down to monolayer [13]. Its excellent sustainability and performance prompt people to use it in ferroelectric applications such as non-volatile memristor [14]. Furthermore, the coexistence of out-of-plane and inplane piezoelectricity in In 2 Se 3 makes it promising in energy harvesting system and self-power nanodevice responding to strain from all directions [15].…”
Section: Introductionmentioning
confidence: 99%